Early activated hepatic stellate cell-derived molecules reverse acute hepatic injury - Chang, Wen-Ju (World J Gastroenterol, 2015)
AIM: To test whether hepatic stellate cells (HSCs) at different activation stages play different roles in acetaminophen (APAP)-induced acute liver injury (ALI). METHODS: HSCs were isolated from mouse liver and cultured in vitro. Morphological changes of initiation HSCs [HSCs (5d)] and perpetuation HSCs [HSCs (p3)] were observed by immunofluorescence and transmission electron microscopy. The protective effects of HSC-derived molecules, cell lysates and HSC-conditioned medium (HSC-CM) were tested in vivo by survival and histopathological analyses. Liver injury was determined by measuring aminotransferase levels in the serum and by histologic examination of tissue sections under a light microscope. Additionally, to determine the molecular mediators of the observed protective effects of initiation HSCs, we examined HSC-CM using a high-density protein array. RESULTS: HSCs (5d) and HSCs (p3) had different morphological and phenotypic traits. HSCs (5d) presented a star-shaped appearance with expressing α-SMA at non-uniform levels between cells. However, HSCs (p3) evolved into myofibroblast-like cells without lipid droplets and expressed a uniform and higher level of α-SMA. HSC-CM (5d), but not HSC-CM (p3), provided a significant survival benefit and showed a dramatic reduction of hepatocellular necrosis and panlobular leukocyte infiltrates in mice exposed to APAP. However, this protective effect was abrogated at higher cell masses, indicating a therapeutic window of effectiveness. Furthermore, the protein array screen revealed that HSC-CM (5d) was composed of many chemokines and growth factors that correlated with inflammatory inhibition and therapeutic activity. When compared with HSC-CM (p3), higher levels of monocyte chemoattractant protein-1, macrophage inflammatory protein-1γ, hepatocyte growth factor, interleukin-10, and matrix metalloproteinase-2, but lower levels of stem cell factor and Fas-Ligand were observed in HSC-CM (5d). CONCLUSION: These data indicated that initiation HSCs and perpetuation HSCs were different in morphology and protein expression, and provided the first experimental evidence of the potential medical value of initiation HSC-derived molecules in the treatment of ALI.